Cancer incidence and mortality trends in Australian adolescents and young adults, 1982–2007 - Haggar, Fatima A; Preen, David B; Pereira, Gavin; Holman, Cashel D; Einarsdottir, Kristjana (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Increasing incidence and lack of survival improvement in adolescents and young adults (AYAs) with cancer have led to increased awareness of the cancer burden in this population. The objective of this study was to describe overall and type-specific cancer incidence and mortality trends among AYAs in Western Australia from 1982–2007. Methods Age–adjusted incidence and mortality rates were calculated for all malignancies combined and for each of the most common diagnostic groups, using five-year age–specific rates. Joinpoint regression analysis was used to derive annual percentage changes (APC) for incidence and mortality rates. Results The annual incidence rate for all cancers combined increased in males from 1982 until 2000 (APC = 1.5%, 95%CI: 0.9%; 2.1%) and then plateaued, whilst rates for females remained stable across the study period (APC = −0.1%; 95%CI: −0.2%; 0.4%) across the study period. For males, significant incidence rate increases were observed for germ cell tumors, lymphoblastic leukemia and thyroid cancer. In females, the incidence of Hodgkin’s lymphoma, colorectal and breast cancers increased. Significant incidence rate reductions were noted for cervical, central nervous system and lung cancers. Mortality rates for all cancers combined decreased from 1982 to 2005 for both males (APC = −2.6%, 95%CI:−3.3%;−2.0%) and females (APC = −4.6%, 95%CI:−5.1%;−4.1%). With the exception of bone sarcoma and lung cancer in females, mortality rates for specific cancer types decreased significantly for both sexes during the study period. Conclusions Incidence of certain AYA cancers increased, whilst it decreased for others. Mortality rates decreased for most cancers, with the largest improvement observed for breast carcinomas. Further research is needed to identify the reasons for the increasing incidence of certain cancers.